Perceived Discrimination and Intergroup Behaviors: The Role of Muslim and American Identity Integration - Saleem, Muniba (Journal of cross-cultural psychology, 2018)
In this article, we test the proposition that identity integration—or perceptions of compatibility versus conflict between one’s social identities—predicts behaviors in intergroup contexts. Using a sample of 171 Muslim Arab American adolescents aged 13 to 19, we examine the relations between identity integration of Muslim and American identities, experiences of discrimination, and intentions to avoid and approach members of the majority group. For adolescents who perceived their American and Muslim identities as being in conflict, we found that perceived discrimination was positively related to intentions to avoid the majority group. However, this trend was not significant for those who perceived their American and Muslim identities as highly integrated. These effects held after controlling for participants’ strength of identification with both American and Muslim identities, and number of years lived in the United States. These results provide support for the idea that identity integration among stigmatized minorities may buffer the negative effects of discrimination on intergroup behaviors.